2003
DOI: 10.1074/jbc.m305546200
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of the Op18/Stathmin-Tubulin Interaction

Abstract: Op18/stathmin (stathmin) is an intrinsically disordered protein involved in the regulation of the microtubule filament system. One function of stathmin is to sequester tubulin dimers into assembly incompetent complexes, and recent studies revealed two tubulin binding sites per stathmin molecule. Using high sensitivity isothermal titration calorimetry, we document that at 10°C and under the conditions of 80 mM PIPES, pH 6.8, 1 mM EGTA, 1 mM MgCl 2 , 1 mM GTP these two binding sites are of equal affinity with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 47 publications
5
49
0
Order By: Relevance
“…The D1-binding site does not overlap with that of RB3-SLD, is exclusively located on β-tubulin, and is distant by more than 40 Å from the α-β interface where the main differences between curved and straight tubulin are located. Taken together with the similar affinities of D1 for GDP-and GTP-tubulin and with a range of other biochemical evidence (11,33), our structural data further support the notion that GTP-tubulin in solution is curved similarly to GDP-tubulin and straightens only as it incorporates in microtubules. This result 2 (marked with an *) is an average of (+)-and (−) end growth velocity, because the two ends could not be distinguished due to similar growth velocities in this condition.…”
Section: Discussionsupporting
confidence: 65%
“…The D1-binding site does not overlap with that of RB3-SLD, is exclusively located on β-tubulin, and is distant by more than 40 Å from the α-β interface where the main differences between curved and straight tubulin are located. Taken together with the similar affinities of D1 for GDP-and GTP-tubulin and with a range of other biochemical evidence (11,33), our structural data further support the notion that GTP-tubulin in solution is curved similarly to GDP-tubulin and straightens only as it incorporates in microtubules. This result 2 (marked with an *) is an average of (+)-and (−) end growth velocity, because the two ends could not be distinguished due to similar growth velocities in this condition.…”
Section: Discussionsupporting
confidence: 65%
“…Fractions containing stathmin were then pooled and dry-lyophilized. Stathmin was resuspended and its concentration determined by the Lowry method with DC Protein Assay (Bio-Rad) and then adjusted, after ITC experiments, to reach the expected stathmin:tubulin stoichiometry of 0.5 [16].…”
Section: Protein Purificationsmentioning
confidence: 99%
“…Experimental temperature was chosen to maximize DH values and to compare our results with previously published data [16]. Tubulin concentrations in the calorimetric cell ranged from 5 to 20 lM, whereas the ligand (VLB or stathmin) concentrations varied from 50 to 200 lM.…”
Section: Itcmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the N-terminal structure could determine affinity and accessibility of STMN1 interactions, because the majority of phosphorylation sites reside in the N-terminus. It was also suggested that N-terminal STMN1 may be intrinsically unstructured, and the molecule could depend on phosphorylation-induced conformation changes for activation (23).…”
Section: Stmn1 Interactions and S25/38 Phosphorylation Determine Prommentioning
confidence: 99%